Performance Investigation of Different Topologies of 1-100 GHz on-chip Transformers using 130 nm SiGe BiCMOS - Gomha, S.; Langat, K. (Engineering, Technology & Applied Science Research, 2019)
In this study, modeling and designing different topologies of on-chip transformers are presented using 130nm SiGe BiCMOS technology. Interleaved, stacked, and full symmetrical interleaved transformers are investigated. Octagon and square shapes are used for designing transformers with flipped and non-flipped feed lines. A comparison between performances of various configurations is presented using a full-wave simulator. The octagon stacked transformer with flipped feed lines showed a good performance at around 60GHz. The simulated results demonstrated a coupling factor K of 0.94, minimum insertion loss of 1.01518dB, and Q-factor of 9 with a minimum occupied area of 0.0019mm2.